Kajian Penjadwalan PLTA Pompa Dengan Metode Gradient Pada Sistem Tenaga Listrik - Abdul Multi (Rekayasa Teknologi, 2011)
This paper presents the study of scheduling pumped storage unit based on the Gradient method. After optimizing hydro-thermal units existed in the system, the problem is to determine the scheduling of pumped storage unit. This paper concentrates on the study of solution methodology for pumped-storage. A pumped-storage unit can be operated in generation, pumping or idle states. It can smooth peak loads and provide spinning reserve, therefore plays an important role in reducing total generation costs. There are, however, many constraints limiting the operation of a pumped-storage unit, such as reservoir volume, inflow and discharge of hydro plant. It saves fuel costs by generating during peak load with water in the upper reservoir, which would be pumped up during light load hours.